Context storage using NoSQL - Santos, Nuno Filipe Vieira dos (2012)
This thesis proposes the usage of an upcoming new breed of databases, called NoSQL, for the storage and management of context information, in a context management architecture based on XCoA (XMPP-based Context Architecture). In this context management architecture all context information is published on a central component called Context Broker, and stored for further requisition, processing and analysis. Due to the high number of published context data, traditional databases quickly develop serious performance limitations, which in turn may jeopardize the XMPP protocol’s efficiency; alternatively, NoSQL databases show serious performance improvements in the storage and management of large-scale data sets. This thesis presents a study of the several available NoSQL solutions, and presents the advantages and disadvantages of the usage of a specific solution in this type of problem.